Leading Change without Formal Authority: The ICC model for the 21st century - Freeman, Homa; Barnes, Lisa; Long, Warrick (Advances in Social Sciences Research Journal, 2021)
Change seems to be a constant feature of the 21st century workplace. Successful organisations embrace change and make sure the personnel are valued, and that they remain engaged and motivated. Employers do not require to formally be in charge of a group of people to be called leader, but demonstrating leadership is an important feature for employees at every level of an organization. Women face a diverse range of difficulties in today’s workplace, and therefore this study aims to focus on the phenomenon of leading change without formal authority and develop a model for women to bring about change within their working climate. This conceptual research aims to identify novel connections between the concepts of leadership and feminism and in consideration of the features of the 21st century workplace. Reviewing the relevant literature particularly around the leadership qualities (drive, motivation, honesty, self-confidence, cognitive ability, and knowledge of the business) this study proposes dedication, political skill and sincerity as qualities of leadership without formal authority. Since, male and female personalities appear to be different in a number of aspects, the basic five personality qualities (known as the Big Five) are reviewed: neuroticism, extraversion, openness, agreeableness, and conscientiousness. Reviewing models of change as well as females’ qualities, this study suggests a model for leading change without formal authority including Identifying gaps, Connecting with emotions, and Committing to change (ICC model).